Asthma Medication Regimens in Pregnancy: Longitudinal Changes in Asthma Status - Rohn, Matthew C.H.; Stevens, Danielle R.; Kanner, Jenna; Nobles, Carrie; Chen, Zhen; Grantz, Katherine L.; Sherman, Seth; Grobman, William A.; Kumar, Rajesh; Biggio, Joseph; Mendola, Pauline (American Journal of Perinatology, 2021)
Objective This study aimed to assess the impact of common asthma medication regimens on asthma symptoms, exacerbations, lung function, and inflammation during pregnancy.Study Design A total of 311 women with asthma were enrolled in a prospective pregnancy cohort. Asthma medication regimen was categorized into short-acting β agonist (SABA) alone, SABA + inhaled corticosteroid (ICS), SABA + ICS + long-acting β agonist (LABA), and no asthma medications (reference). We evaluated asthma control at enrollment (< 15 weeks' gestation) and its change into trimesters 2 and 3, including per cent predicted forced expiratory volume in 1 second (%FEV1) and peak expiratory flow (%PEF), pulse oximetry, fractional exhaled nitric oxide (FeNO), asthma symptoms (asthma attacks/month, night symptoms/week), and severe exacerbations. Linear mixed models adjusted for site, age, race, annual income, gestational age, body mass index, and smoking, and propensity scores accounted for asthma control status at baseline.Results Women taking SABA + ICS and SABA + ICS + LABA had better first trimester %PEF (83.5% [75.7–91.3] and 84.6% [76.9–92.3], respectively) compared with women taking no asthma medications (72.7% [66.0–79.3]). Women taking SABA + ICS + LABA also experienced improvements in %FEV1 (+11.1%, p < 0.01) in the third trimester and FeNO in the second (−12.3 parts per billion [ppb], p < 0.01) and third (−11.0 ppb, p < 0.01) trimesters as compared with the trajectory of women taking no medications. SABA + ICS use was associated with increased odds of severe exacerbations in the first (odds ratio [OR]: 2.22 [1.10–4.46]) and second (OR: 3.15 [1.11–8.96]) trimesters, and SABA + ICS + LABA use in the second trimester (OR: 7.89 [2.75–21.47]). Women taking SABA alone were similar to those taking no medication.Conclusion Pregnant women taking SABA + ICS and SABA + ICS + LABA had better lung function in the first trimester. SABA + ICS + LABA was associated with improvements in lung function and inflammation across gestation. However, both the SABA + ICS and SABA + ICS + LABA groups had a higher risk of severe exacerbation during early to mid-pregnancy.Key Points
Keywords: asthma; pregnancy; medication